Field test study and operation strategy research on chilled water storage air conditioning system - Dongliang Zhang; Jiankun Yang; Maokun Sun; Xueying Xia (International Journal of Sustainable Energy)
The objectives of this paper were to: (i) analyze field testing results to find the reason of current unreasonable operation strategy; (ii) propose operation strategy based on the above work and demonstrate its effectiveness. The results indicated that, unreasonable operation strategies were mainly due to the mismatching of chilled water storage capacity and user side cooling demand. And heat pumps inefficiently operating under low part load ratio (PLR) condition from 11:00 to 19:00 in design day resulted in high operation cost, too. In this paper, proposed operation strategy considered operation objective, operation constraints, time of use electricity price and heat pumps efficient operation. Compared to current operation strategy, proposed operation strategy yielded 30.5% operation cost saving in design day and 15.1% seasonal operation cost saving in summer. Proposed operation strategy is effective to guide system actual operation.